2021
DOI: 10.1097/pts.0000000000000914
|View full text |Cite
|
Sign up to set email alerts
|

What Severe Medication Errors Reported to Health Care Supervisory Authority Tell About Medication Safety?

Abstract: Objectives This study investigated severe medication errors (MEs) reported to the National Supervisory Authority for Welfare and Health (Valvira) in Finland and evaluated how the incident documentation applies to learning from errors. Methods This study was a retrospective document analysis consisting of medication-related complaints and authoritative statements investigated by Valvira in 2013 to 2017 (n = 58). Results Medication errors cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In more than half of the cases (52%, n = 30), the ME caused the patient’s death or severe harm. Other characteristics of the data have been published elsewhere [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In more than half of the cases (52%, n = 30), the ME caused the patient’s death or severe harm. Other characteristics of the data have been published elsewhere [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main researcher made notes of those MEs for detecting possible missing categories in the aggregated DRP classification system. Because severe MEs are often complex processes including several errors [ 16 , 17 , 31 , 32 ], all identified MEs were categorized from description of each case.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective study stated that 52% of cases of medication errors reported to the National Monitoring Authority for Welfare and Health in Finland resulted in death or worsening conditions. The study also said that as much as 47% of them occurred in terms of drug prescribing [10] . Medication errors can occur in every step of the treatment process, both in the processes of prescribing, reading prescriptions (transcription), preparing for drug delivery (dispensing), and using drugs (administration) [11] .…”
Section: Introductionmentioning
confidence: 84%
“…Many reported medical errors and incidents are related to pharmaceutical products [1][2][3]. Pharmaceutical products come in various dosage forms including infusions, injections, powders, tablets, and patches.…”
Section: Introductionmentioning
confidence: 99%